La inocuidad: principio informante y de adecuación de deberes preventivos y buenas prácticas en la atención remota y presencial del consumidor durante el contexto de la pandemia de COVID-19 - Isler Soto, Erika (2020)
As the principle of safety is an informing guideline in the Consumer Protection Law, this text reviews its concretization in the rights, duties and good practices that take place with regard to consumer care in the context of the COVID-19 pandemic. With that objective, it begins with an approach to the pandemic and its main characteristics. Subsequently, the safety principle is explained in relation to three aspects: The consumer’s personal and patrimonial integrity, and its main characteristics; its scope in the Chilean consumer protection system; and the notion of vulnerable consumer as an adequacy criterion. This topic is then explained in a general way and with regard to remote and face-to-face market. In that sense, this study postulates that, in all these dimensions, the behavior of suppliers and consumers must be adjusted to the safety imperatives that prevent risk for the consumer and the rest of the country. That is derived from the character of public order that has the protection of the personal and patrimonial integrity of the consumer.